Building prosperity Australia's future as a global player - Kasper, Wolfgang (Centre for Independent Studies, 2000)
The author argues that periods of plenty are the best time to prepare for eventualities by cutting back on unnecessary government activity and placing economic freedom on more solid foundations. He warns that the present phase of high worldwide economic growth is likely to peter out before too long.